1981
DOI: 10.1007/bf00433508
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of hypothermia and behavioral response to apomorphine: A simple, rapid and discriminating test for screening antidepressants and neuroleptics

Abstract: The antagonism of hypothermia induced by two doses of apomorphine (1 to 16 mg/kg) is proposed as an improved screening test for both neuroleptics and antidepressants. Low dose apomorphine-induced hypothermia (1 mg/kg) differentiates sulpiride-like neuroleptics (which better antagonize this effect of apomorphine than other effects such as stereotyped behavior) from haloperidol-like drugs. The latter equally antagonize the two effects of apomorphine. The effects of sulpiride are also distinct from those of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…Inhibition of hypothennia induced by high dose apomorphine is also a frequently used method for detecting antidepressant activity and EGYT-4201 proved to be effective in this model as well. However, its potency did not reach that of other antidepressants cited in the literature [Puech et al, 1981;Pawlowski and Mazela, 19861. The compound was also active in potentiation of the effect of L-dopa and D-amphetamine, although it showed only moderate activity.…”
Section: Discussionmentioning
confidence: 89%
“…Inhibition of hypothennia induced by high dose apomorphine is also a frequently used method for detecting antidepressant activity and EGYT-4201 proved to be effective in this model as well. However, its potency did not reach that of other antidepressants cited in the literature [Puech et al, 1981;Pawlowski and Mazela, 19861. The compound was also active in potentiation of the effect of L-dopa and D-amphetamine, although it showed only moderate activity.…”
Section: Discussionmentioning
confidence: 89%
“…At noradrenergic terminals apomorphine acting through D 2 receptors prevents noradrenaline release. Puech et al (1981) showed that hypothermia induced by high doses of apomorphine is antagonized by antidepressants. Different animal models often require different doses of the same drug, in order to show any effect.…”
Section: Discussionmentioning
confidence: 99%
“…Apomorphine treatment causes a decrease in the rectal temperature and this effect is prevented by antidepressive drugs such as imipramine (Puech et al, 1981). In order to confi rm a possible antidepressive effect of the H. pectinata AE, we tested the effects of apomorphine in rectal temperature of mice treated with the plant AE.…”
Section: Apomorphine-induced Hypothermiamentioning
confidence: 99%
“…With regard to the effects of these infusions on the hypothermia induced by high-dose apomorphine (16 mg/kg s.c.), none of the infusions showed a significant decrease of the hypothermia induced by the drug compared with the control (Table 4), at variance with the standard drug imipramine. Nevertheless, H. grandifolium infusion antagonized (but not significantly) in 30% of mice the hypothermia induced by apomorphine 30 and 60 min after administration, indicating a possible inhibition of norepinephrine reuptake (Puech et al, 1981).…”
Section: Antidepressant Activitymentioning
confidence: 98%